2018
DOI: 10.1093/nar/gky893
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage to epigenetically methylated sites affects DNA stability, dynamics and enzymatic demethylation

Abstract: DNA damage can affect various regulatory elements of the genome, with the consequences for DNA structure, dynamics, and interaction with proteins remaining largely unexplored. We used solution NMR spectroscopy, restrained and free molecular dynamics to obtain the structures and investigate dominant motions for a set of DNA duplexes containing CpG sites permuted with combinations of 5-methylcytosine (mC), the primary epigenetic base, and 8-oxoguanine (oxoG), an abundant DNA lesion. Guanine oxidation significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 78 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…We showed that bisphenol exposure quickly induces the formation (Hörandl & Hadacek, 2013;Pan et al, 2016). Second, oxidized guanine biases the recognition of methylated CpG dinucleotides and alters the dynamic of DNA demethylation (Gruber et al, 2018;Pan et al, 2016). Interestingly, acquisition of the meiotic competence is completely dependent on an intensive germinal DNA demethylation (Hargan-Calvopina et al, 2016b;Yamaguchi et al, 2012).…”
Section: Badge or Bpaf Fetal Exposures Alter Dna Demethylation In Pgcsmentioning
confidence: 90%
“…We showed that bisphenol exposure quickly induces the formation (Hörandl & Hadacek, 2013;Pan et al, 2016). Second, oxidized guanine biases the recognition of methylated CpG dinucleotides and alters the dynamic of DNA demethylation (Gruber et al, 2018;Pan et al, 2016). Interestingly, acquisition of the meiotic competence is completely dependent on an intensive germinal DNA demethylation (Hargan-Calvopina et al, 2016b;Yamaguchi et al, 2012).…”
Section: Badge or Bpaf Fetal Exposures Alter Dna Demethylation In Pgcsmentioning
confidence: 90%
“…It is possible that DNA and polymerase active site distortions similar with revealed in the G. stearothermophilus Pol I structure with oxoG:C pair [69] can provide a basis for oxoG:C recognition by a specialized DNA polymerase and facilitate polymerase switching to extend the correct oxoG:C pair. It cannot be excluded that the local destabilizing effect of oxoG on DNA [74,75] and less stable base pairing [68] might also promote a high-fidelity polymerase pausing and switching to a specialized DNA polymerase during replication and TLS. In MUTYH-dependent BER pathway, recruitment of specialized DNA polymerases to the oxoG or oxoG:A lesion sites can be mediated by specific protein-protein interactions with repair enzymes and regulatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…The syn conformation of the lesion exposes the HG edge for H-bonding with the incoming dATP nucleotide in the anti conformation generating a pair similar to (anti)T:(anti)A structurally. Since the pro-mutagenic (syn)oxoG:(anti)A mispair mimics the geometry of a correct base pair, it does not cause significant Interestingly, while X-ray and NMR structures show that DNA with oxoG lesion appears virtually identical to the corresponding unmodified duplex and the oxoG:C has a normal high-affinity Watson-Crick base pairing arrangement, thermodynamic studies indicate that oxoG has a local destabilizing effect on DNA (destabilizes oxoG:C and 5' flanking base pairs) [74,75]. The origin of this destabilization was attributed to the loss of a cation-binding site in the major groove (due to the replacement of an electronegative N7 with an electropositive N-H), reduction in the level of hydration and reduced base stacking [74] and to steric repulsion effects that propagate from O 8 via the sugar pucker to the 3 -phosphate [75,76].…”
Section: The Structural Basis Of Ambiguous Coding Potential Of Oxogmentioning
confidence: 99%
“…A special type of NMR, namely methyl-transverse relaxation optimized NMR (methyl-TROSY) is more suitable for the investigation of subtle dynamic changes, which is more typical for the histone tail-reader protein interactome [101]. The NMR linewidths of the base imino protons of DNA provide an informative insight into base pair opening dynamics [105]. A broader line shows reduced base pair stability and increased base pair opening rates, for example, oxidation of guanine led to line broadening of guanine base imino protons, and methylation of cytosine resulted in imino proton line narrowing [105], indicating that cytosine methylation stabilizes the DNA duplex.…”
Section: Trendsmentioning
confidence: 99%
“…The NMR linewidths of the base imino protons of DNA provide an informative insight into base pair opening dynamics [105]. A broader line shows reduced base pair stability and increased base pair opening rates, for example, oxidation of guanine led to line broadening of guanine base imino protons, and methylation of cytosine resulted in imino proton line narrowing [105], indicating that cytosine methylation stabilizes the DNA duplex. Solid state NMR can determine the binding sites on the nucleosome surface, and demonstrate the dynamic nature of the N and C terminal tails of histones within the core octamer [106].…”
Section: Trendsmentioning
confidence: 99%